Internal stress due to solvent co-intercalation in graphite electrodes for Li ion batteries. (December 2016) - Sheldon, Brian W.; Tokranov, Anton
Abstract: Thin film graphite electrodes were investigated in Li half-cells, to investigate the stresses induced by propylene carbonate (PC) additions to a standard liquid electrolyte. In situ wafer curvature measurements indicate that substantial compressive stress occurs above 0.5 V, before there is significant Li intercalation into the graphite. Transmission electron microscopy shows that this cycling produces voids throughout the film, via delamination between graphene layers. To explain these observations, a model based on interlaminar debonding and the subsequent buckling of graphite layers is proposed. Existing mechanics models of these phenomena are in good agreement with the experimental observations. Based on this analysis, it appears that the PC additions lead to a very low value of the interlaminar fracture resistance.